2010
DOI: 10.2139/ssrn.1708079
|View full text |Cite
|
Sign up to set email alerts
|

Retirement of Dutch Male Older Workers: The Role of Mid-Life Educational, Work, Health, and Family Experiences

Abstract: Objectives. The life course perspective suggests that the retirement process cannot be understood thoroughly without paying attention to distal life experiences. In empirical studies on predictors of retirement, however, mid-life experiences often have remained implicit or have been neglected. This study aims to improve our understanding of retirement, by studying the impact of mid-life experiences in the educational, work, health, and family life spheres on retirement intentions and behavior.Methods. Using pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As individual International Journal of Ageing and Later Life characteristics have been addressed in earlier research (Blö ndal & Scarpetta 1999;Damman et al 2009;European Commission 2009;Fischer & Sousa-Poza 2006;Hayward et al 1989Hayward et al , 1998Mein et al 2000;OECD 2011;Schils 2008; Von Bohnsdorff 2009), we will not formulate specific hypotheses about their association with participation, but take them into account as control variables. First, the literature identified several so-called push and pull factors.…”
Section: Theoretical Framework Of Labor Market Participationmentioning
confidence: 99%
“…As individual International Journal of Ageing and Later Life characteristics have been addressed in earlier research (Blö ndal & Scarpetta 1999;Damman et al 2009;European Commission 2009;Fischer & Sousa-Poza 2006;Hayward et al 1989Hayward et al , 1998Mein et al 2000;OECD 2011;Schils 2008; Von Bohnsdorff 2009), we will not formulate specific hypotheses about their association with participation, but take them into account as control variables. First, the literature identified several so-called push and pull factors.…”
Section: Theoretical Framework Of Labor Market Participationmentioning
confidence: 99%
“…A recent study of a life course approach to retirement using Dutch longitudinal data clearly showed that retirement is a matter of personal agency within structure over time and that income and wealth are signifi cant variables but they are not the only signifi cant or most important explanatory variables when it comes to explaining retirement. Further, experiences in midlife set the stage for retirement in later life (Damman, Henkens, & Kalmijn, 2010 ).…”
Section: The Theory and Retirement: Edging Forwardmentioning
confidence: 99%
“…While higher education was associated with later retirement in the UK (Schils 2008), the US (Hayward et al 1989(Hayward et al , 1998, and Norway (Blekesaune & Solem 2005), studies in other countries reported the opposite effect (Fischer & Sousa-Poza 2006). Finally, family and partners play a role: individuals who had a partner and those with children appeared to retire earlier in some countries (Damman et al 2009;Schils 2008). Moreover, different strands of literature discussed that individual International Journal of Ageing and Later Life retirement decisions were often taken as a joint decision of spouses (see e.g., Blau 1998;Coile 2004) and that informal care obligations affected retirement planning (see e.g., Dentinger & Clarkberg 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different strands of literature discussed that individual International Journal of Ageing and Later Life retirement decisions were often taken as a joint decision of spouses (see e.g., Blau 1998;Coile 2004) and that informal care obligations affected retirement planning (see e.g., Dentinger & Clarkberg 2002). With regard to work characteristics, studies showed that physical demand (Blekesaune & Solem 2005;Hayward et al 1989Hayward et al , 1998 and part-time work (Damman et al 2009;Hayward et al 1998) decreased labor market participation. Findings regarding compensation were not straightforward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation